2015
DOI: 10.1155/2015/564858
|View full text |Cite
|
Sign up to set email alerts
|

C‐Reactive Protein in Peripheral Blood of Patients with Chronic and Aggressive Periodontitis, Gingivitis, and Gingival Recessions

Abstract: CRP is a plasma protein that reflects a measure of the acute phase response to inflammation and is one of the markers of choice in monitoring this response. CRP can be used for the prediction and early detection of periodontal disease. The aim of this study was to compare and evaluate the systemic levels of CRP in the peripheral blood samples of patients with chronic and aggressive periodontitis, gingivitis, and gingival recessions and compare them with periodontal clinical parameters. All patients (N = 158) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…In subjects with gingivitis, the severity and extent of gingival inflammation were evaluated for their relationship with CRP levels in serum. While in some studies CRP levels were found to be significantly positively correlated with papillary bleeding index or GI, other authors failed to find an association between CRP levels and GI, BOP, or the number of sextants with at least one BOP+ site . Certain factors may have contributed to the heterogeneity among these findings.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In subjects with gingivitis, the severity and extent of gingival inflammation were evaluated for their relationship with CRP levels in serum. While in some studies CRP levels were found to be significantly positively correlated with papillary bleeding index or GI, other authors failed to find an association between CRP levels and GI, BOP, or the number of sextants with at least one BOP+ site . Certain factors may have contributed to the heterogeneity among these findings.…”
Section: Methodsmentioning
confidence: 95%
“…Among the investigated biomarkers, particular attention has been paid to C‐reactive protein (CRP), which is produced in response to many forms of trauma or diseases and contributes to host defense as part of the innate immune response. Studies that evaluated the association between gingivitis and serum levels of CRP universally identified gingivitis as a condition characterized by serum CRP levels which are intermediate between those measured in periodontal health and periodontitis, although differences in serum CRP levels observed between gingivitis and the other periodontal conditions did not consistently reach statistical significance in all studies . In subjects with gingivitis, the severity and extent of gingival inflammation were evaluated for their relationship with CRP levels in serum.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this T. denticola has also been designated as a keystone pathogen. Excellent reviews, too many to list here, are available detailing the roles that P. gingivalis, T. denticola and other bacteria play in periodontal disease (Darveau 2010;Dashper et al 2010;How et al 2016;McDowell et al 2012;Mysak et al 2014;Podzimek et al 2015;Sharma 2010). …”
Section: Expansion Of the Bacterial Complex Conceptmentioning
confidence: 99%
“…19,45 Further, GPRC6A was identified by GWAS as a locus associated with circulating C‐reactive protein (CRP), which is a general marker of chronic systemic inflammation . Podzimek et al . reported the highest CRP levels in AgP patients when compared with gingivitis or CP patients and also showed a correlation of increased CRP levels with the severity of periodontitis and BoP.…”
Section: Discussionmentioning
confidence: 99%